Development And Evaluation Of Nanogel System Loaded With Triclosan And Flurbiprofen For Treatment Of Periodontitis - Nafiu, Aminu (2019)
Periodontitis is a highly prevalent major dental disease that affects millions of people around the globe. Anaerobic gram-negative bacteria and its toxins have been strongly implicated as a prime cause of the disease. A great number of local drug delivery systems have been proposed, but they were mainly made to focus on killing the causative microbes rather than also targeting the inflammation which also plays a significant role in the aetiology of the disease. Moreover, there is difficulty in accessing the periodontal pocket and attaining adequate residence time by these systems, hence being only partially successful. Therefore, the aim of this study was to formulate and evaluate a novel biocompatible nanogel (NG) co-loaded with triclosan (TCS) and flurbiprofen (FLB) for effective intra-pocket treatment of periodontitis. TCS and FLB are highly crystalline compounds and practically insoluble in water. These properties restrict delivery of their pure forms into the periodontal pocket, hence warranted their formulation into a nanoparticulate system. HPLC method development, compatibility study, nanoparticles (NPs) and NG development were performed. The formulations were extensively characterised by scanning electron microscopy (SEM), transmission electron microscopy (TEM), particle size, polydispersity index (PDI), zeta potential, differential scanning calorimetry (DSC), X-ray powder diffraction (XRPD), fourier transform infrared spectroscopy (FTIR), rheology, swelling, erosion, bioadhesion, in vitro release, antimicrobial, stability and in vivo studies. The developed HPLC method was able to successfully separate and quantify TCS and FLB at retention times (tR) of 12.5 and 10.1 min, respectively.